(untitled) (Research, Society and Development, 2021)
The objective of this work was to research Coliforms and Escherichia coli in coconut water sold by street vendors in the city of Fortaleza, Ceará. For this, five samples of coconut water sold by street vendors at traffic lights on busy avenues were acquired as a consumer. The samples were taken to the food analysis laboratory of a University Center to investigate the presence or absence of coliforms and Escherichia coli, using the methodology described by the Compendium of Methods for the Microbiological Examination of Foods of the American Public Health Association (APHA, 2001). It was observed that the microbiological quality of the coconut water in question reported irregularities, but with only one sample totally out of the standard. Considering the results, it is clear the need to apply good handling practices during the extraction, filling and storage of coconut water sold by street vendors so that there is more safety in the consumption of this product by the population.